Metabolomics-based exploration the response mechanisms of Saussurea involucrata leaves under different levels of low temperature stress - Qi Sun; Lihua Ma; Xinxia Zhu (BMC Genomics, 2023)
Abstract Background Saussurea involucrata (Sik.) is alpine plant that have developed special adaptive mechanisms to resist adverse environmental conditions such as low temperature chilling during long-term adaptation and evolution. Exploring the changes of its metabolites under different temperature stresses is helpful to gain insight into its cold stress tolerance. Methods Ultra-performance liquid chromatography and tandem mass spectrometry were used to analyze the metabolites in the leaves of Sik. under low different temperature stress conditions. Results: A total of 753 metabolites were identified, and 360 different metabolites were identified according to the Kyoto Encyclopedia of Genes and Genomes (KEGG) involved in the biosynthesis of secondary metabolites and amino acids and sugars. Sucrose and trehalose synthesis, glycolysis, tricarboxylic acid cycle, pentose phosphate pathway, glutamic acid-mediated proline biosynthesis, purine metabolism, amino acid metabolism, phenylpropane synthesis pathway metabolites all respond to low temperature stress. Under cold stress conditions, carbohydrates in Sik. leaves accumulate first than under freezing conditions, and the lower the temperature under freezing conditions, the less amino acids accumulate, while the phenolic substances increase. The expression of various substances in LPE and LPC increased more than 10-fold after low temperature stress compared with the control, but the content of LPE and LPC substances decreased after cold adaptation. In addition, purines and phenolics decreased and amino acids accumulated significantly under freezing conditions. Conclusion: The metabolic network of Sik. leaves under different low temperature stress conditions was proposed, which provided a reference for further exploration of the metabolic mechanism related to low temperature stress tolerance of Sik.